2022
DOI: 10.1038/s41560-022-01076-9
|View full text |Cite
|
Sign up to set email alerts
|

A universal close-space annealing strategy towards high-quality perovskite absorbers enabling efficient all-perovskite tandem solar cells

Abstract: A universal close-space annealing strategy towards high-quality perovskite absorbers enabling efficient all-perovskite tandem solar cells. Nature Energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 162 publications
(115 citation statements)
references
References 43 publications
1
114
0
Order By: Relevance
“…[8] The large V OC -deficit (defined as E g /q-V OC ) in WBG PSCs is commonly attributed to the relatively low initial radiative efficiency of the cells due to the high defect densities within the perovskite absorber layer and at the perovskite/charge selective layer interface. Over the past years, many approaches, including compositional engineering, [9][10][11][12] additive engineering, [13][14][15] interfacial engineering, [16][17][18] and mixed-dimensional engineering, [19][20][21][22] have been explored and the V OC -deficit has been reduced to values as low as 0.37 V in PSCs with bandgap (≈1.72 eV) suitable for perovskite-Si tandems. [23] However, extending these strategies to mitigate the V OC -deficit in perovskites with even wider bandgaps (≈1.80 eV) that are required for two-terminal (2T) all-perovskite tandems remains very challenging.…”
Section: Introductionmentioning
confidence: 99%
“…[8] The large V OC -deficit (defined as E g /q-V OC ) in WBG PSCs is commonly attributed to the relatively low initial radiative efficiency of the cells due to the high defect densities within the perovskite absorber layer and at the perovskite/charge selective layer interface. Over the past years, many approaches, including compositional engineering, [9][10][11][12] additive engineering, [13][14][15] interfacial engineering, [16][17][18] and mixed-dimensional engineering, [19][20][21][22] have been explored and the V OC -deficit has been reduced to values as low as 0.37 V in PSCs with bandgap (≈1.72 eV) suitable for perovskite-Si tandems. [23] However, extending these strategies to mitigate the V OC -deficit in perovskites with even wider bandgaps (≈1.80 eV) that are required for two-terminal (2T) all-perovskite tandems remains very challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Li and co-workers developed a close-space annealing (CSA) strategy, which involves covering the intermediatephase perovskite with a solvent-permeable film during the annealing process. 32 In comparison with the normal annealing, the CSA method slowed the vertical solvent-escape rate and led to recrystallization of grains and a smooth surface. This approach enabled the fabrication of a Pb−Sn perovskite solar cell (PSC) with a 21.5% PCE.…”
Section: Optimization Of Perovskite Absorbersmentioning
confidence: 99%
“…More recently, Wang et al [19] focused on the fast crystallization for mixed Pb-Sn perovskites and reported a facile film side down close-space annealing (CSA) process to improve the quality of perovskite absorbers. The CSA strategy improved the performance of both NBG and WBG subcells, leading to the highest PCE of 25.05% for tandem cells.…”
Section: Narrow-bandgap Subcellmentioning
confidence: 99%